High parity and chronic energy deficiency increase risk for low birth weight in Situbondo District - Dyah Ekowati; Luh Seri Ani; I Gusti Ayu Trisna Windiani (Public Health and Preventive Medicine Archive, 2017)
Background and purpose: The prevalence of low birth weight (LBW) in Situbondo District increased from 2.79% in 2008 to 5.85% in 2014. The highest prevalence in 2015 was found in Bungatan Subdistrict (11%). This study aims to determine risk factors of LBW in Bungatan Subdistrict, Situbondo. Methods: A case control study was conducted in Bungatan Subdistrict. A total of 60 infants born at the Bungatan Public Health Centre were included in the study. Cases were infants with LBW and controls were those with normal birth weight. All infants born with LBW were taken as cases (20 infants) while 40 controls were selected using a systematic random sampling. Data were collected from February to March 2016. Data were analysed using bivariate and multivariate technique with logistic regression test. Results: The majority of respondents were unemployed (80%), aged between 20-35 years during the pregnancy (53.33%), with parity of ≤3 (66.67%), low education level (61.67%), anemia during the pregnancy (68.33%), good nutritional status (75.00%), poor nutrition intake during the pregnancy (51.67%) and without pre-eclampsia (88.33%). Parity of >3 increased the risk of LBW (AOR=6.4; 95%CI: 1.66-24.75). Chronic energy deficiency increased the risk of LBW (AOR=5.6; 95%CI: 1.41-22.57). Conclusions: Parity of more than three and chronic energy deficiency increase the risk for LBW in Bungatan Public Health Centre, Situbondo District.